In vitro effects on biofilm viability and antibacterial and antiadherent activities of silymarin - Evren, Ebru; Yurtcu, Erkan (Folia microbiologica, 2015)
Limited treatment options in infectious diseases caused by resistant microorganisms created the need to search new approaches. Several herbal extracts are studied for their enormous therapeutic potential. Silymarin extract, from Silybum marianum (milk thistle), is an old and a new remedy for this goal. The purpose of this study is to evaluate the antibacterial and antiadherent effects of silymarin besides biofilm viability activity on standard bacterial strains. Minimal inhibitory concentration (MIC), minimal bactericidal concentration (MBC), antiadherent/antibiofilm activity, and effects on biofilm viability of silymarin were evaluated against standard bacterial strains. MIC values were observed between 60 and >241 μg/mL (0.25->1 mmol/L). Gram-positive bacteria were inhibited at concentrations between 60 and 120 μg/mL. Gram-negative bacteria were not inhibited by the silymarin concentrations included in this study. MBC values for Gram-positive bacteria were greater than 241 μg/mL. Adherence/biofilm formations were decreased to 15 μg/mL silymarin concentration when compared with silymarin-untreated group. Silymarin reduced the biofilm viabilities to 13 and 46 % at 1 and 0.5 mmol/L concentrations, respectively. We demonstrated that silymarin shows antibacterial and antiadherent/antibiofilm activity against certain standard bacterial strains which may be beneficial when used as a dietary supplement or a drug.
Keywords: Gram-Positive Bacteria; grampozitivní bakterie; mikrobiální viabilita; Bacterial Adhesion; biofilmy; Silybum marianum; Silymarin; silymarin; Biofilms; Anti-Bacterial Agents; mikrobiální testy citlivosti; Gram-Negative Bacteria; Microbial Sensitivity Tests; bakteriální adheze; ostropestřec mariánský; gramnegativní bakterie; Microbial Viability; antibakteriální látky